S100 Reduction of inflammatory cytokine production in chronic obstructive pulmonary disease (COPD) epithelial cells by protease activated receptor 2 (PAR2) antagonism. (12th November 2019) - Bailo, M; Dunning, L; Brzeszczynska, J; McIntosh, K; Plevin, R; Martin, SL; Sergeant, GP; Goodyear, CS; Litherland, GJ; Lockhart, JC; Crilly, A
Abstract : Inflammatory cytokine production is a hallmark of COPD. PAR2 activation, via the transmembrane serine protease matriptase, results in the regulation of pro-inflammatory cytokines, including IL-6 and IL-8 (Seitz et al ., 2007). The aim of this study was to investigate a putative role for PAR2 in COPD. PAR2 and matriptase expression was determined by immunofluorescence in primary human bronchial epithelial cells derived from healthy controls and COPD patients (HBECs & DHBECs respectively). Levels of secreted IL-6 and IL-8 were evaluated by ELISA. The role of PAR2 in the DHBEC-associated inflammatory response was investigated using the PAR2 antagonist AZ8838 (Cheng et al ., 2017). Immunofluorescent microscopy showed both HBECs and DHBECs express PAR2, whereas only DHBECs express matriptase. Evaluation of spontaneous cytokine secretion revealed that both IL-6 and IL-8 were significantly increased ( P <0.01) in DHBECs compared to HBECs. Importantly, inhibition of PAR2 activation in DHBECs by AZ8838 significantly reduced IL-8 (48 h) and IL-6 (72 h) secretion, figure 1. This study used a recently developed antagonist to demonstrate a role for PAR2 in the regulation of pro-inflammatory cytokine release from COPD bronchial epithelial cells. Since increased protease activity is a feature of COPD, elevated expression of matriptase may contribute to PAR2 activation in this disease. References: Cheng, R. K. Y. et al . ( 2017) 'Structural insight into allosteric modulation of protease-activated receptor 2', Nature . Nature Publishing Group, 545(7652), pp. 112–115. doi: 10.1038/nature22309. Seitz, I. et al . ( 2007) 'Membrane-type serine protease-1/matriptase induces interleukin-6 and -8 in endothelial cells by activation of protease-activated receptor-2: Potential implications in atherosclerosis', Arteriosclerosis, Thrombosis, and Vascular Biology. doi: 10.1161/01.ATV.0000258862.61067.14.